1995
DOI: 10.1128/jvi.69.1.122-130.1995
|View full text |Cite
|
Sign up to set email alerts
|

A human monoclonal antibody to a complex epitope in the V3 region of gp120 of human immunodeficiency virus type 1 has broad reactivity within and outside clade B

Abstract: We have used virus neutralization and antibody-binding techniques to define the epitope for a human monoclonal antibody, designated 19b, within the V3 region of the gp120 surface glycoprotein of human immunodeficiency virus type 1. Unusually, the 19b epitope encompasses residues on both flanks of the V3 loop. However, 19b binding to gp120 is independent of sequences at the crown of the V3 loop, provided that they are compatible with the formation of a type II ␤ turn that is presumably necessary to juxtapose th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(66 citation statements)
references
References 58 publications
4
61
1
Order By: Relevance
“…So, with the exception of clades B and E, which show distinct antigenic differences 121 , there seems to be no particular preference for sera from patients infected with one clade to neutralize other viruses from the same clade; a diagramatic representation of this is shown in FIG. 5. Similarly, studies of HIV-1-specific human monoclonal antibodies, most of which come from clade-B-infected individuals (such as those listed in TABLE 1) show their comparable potency in neutralizing many viruses from various clades 32,86,122 . These data raise important questions about the relevance of HIV-1 genotypic classification in vaccine design.…”
Section: The Need For Polyvalent Vaccinesmentioning
confidence: 92%
“…So, with the exception of clades B and E, which show distinct antigenic differences 121 , there seems to be no particular preference for sera from patients infected with one clade to neutralize other viruses from the same clade; a diagramatic representation of this is shown in FIG. 5. Similarly, studies of HIV-1-specific human monoclonal antibodies, most of which come from clade-B-infected individuals (such as those listed in TABLE 1) show their comparable potency in neutralizing many viruses from various clades 32,86,122 . These data raise important questions about the relevance of HIV-1 genotypic classification in vaccine design.…”
Section: The Need For Polyvalent Vaccinesmentioning
confidence: 92%
“…Defining the epitopes recognized by anti-V3 antibodies has traditionally been accomplished with V3 peptides in ELISA binding assays (e.g. Pepscan) and competition studies, or by determining the ability of the antibodies to bind a series of recombinant gp120s with varying V3 regions (for example (Eda et al, 2006b;Gorny et al, 1992;Gorny et al, 1998;Laisney and Strosberg, 1999;Moore et al, 1994;Moore et al, 1995;Schreiber et al, 1997;Seligman et al, 1996;White-Scharf et al, 1993)). In some instances, the results derived from these studies have been confirmed by analyzing peptide sequences selected with antibody from peptide phage display libraries (Keller et al, 1993) or by comparing the ability of antibodies to neutralize viruses with various V3 sequences (e.g.…”
Section: Effect Of Single-residue Substitutions In the V3 Region Of Gmentioning
confidence: 99%
“…The V3 loop is especially well exposed on monomeric or oligomeric gp120 and is accessible to various neutralizing MAbs but can simultaneously mask some discontinuous, conserved neutralization epitopes (29,51). From the work of several groups, it became evident that in natural infection, antibodies are preferentially produced against discontinuous epitopes on the gp120 glycoprotein (28,30,44,45). The V3 loops of clade B strains have a conserved GPGRAF sequence, called tip of the loop, as well as variable sequences on either side (22).…”
mentioning
confidence: 99%